Pengaruh Literasi Keuangan dan Financial Technology terhadap Kinerja Keuangan pada UMKM Sektor Kuliner Pengguna QRIS di Kecamatan Binawidya - Febriani Zulhia Putri; Ruzikna Ruzikna (Lembaga Pengembangan Kinerja Dosen, 2025)
In the face of increasing business competition, MSMEs must have a competitive advantage such as financial capability and utilize technological innovation in order to continue to achieve the desired business financial performance. This study aims to determine how financial literacy and financial technology affect the financial performance on the QRIS users of culinary sector MSMEs in Binawidya District. This research uses quantitative descriptive methods. The sampling technique used was purposive sampling with a sample size of 79 respondents. The data obtained was processed using SPSS software version 27. The results showed that: (1) Financial literacy has a significant effect on financial performance, (2) financial technology has a significant effect on financial performance, (3) financial literacy and financial technology have a significant effect on the financial performance on the QRIS users of culinary sector MSMEs in Binawidya District